A comparison between metoclopramide and promethazine plus pyridoxine in the management of hyperemesis gra vidarum: a randomized controlled trial - Mohammad, Mazniza'in (2010)
Hyperemesis gravidarum is a debilitating condition, involving the general health and psychological aspects of the patients, as well as creating financial burden to the family. An effective treatment will be very much beneficial in reducing these stressful conditions. The mainstay treatment for hyperemesis gravidarum is to stop the bouts of vomiting, rehydration as well as correcting the starvation state of the patients. A lot of antiemetics have been widely used as the first-line treatment. However, their efficacy has never been compared, thus the aim of this study. This study was performed to compare the efficacy of metoclopramide with the combination of promethazine and pyridoxine as antiemetics in patients with hyperemesis gravidarum. The efficacy of either regime was measured by the mean PUQE score achieved after treatment, the duration taken to clear the ketones in the urine, duration of hospital stay as well as the side- effects encountered. Patients admitted to Ward 1 Utara of Hospital Universiti Sains Malaysia with hyperemesis gravidarum were randomized to receive either metoclopramide 1 Omg three times a day or combination of promethazine 25mg three times a day with pyridoxine 20mg three times a day. The degree of vomiting was assessed by using the PUQE score, performed at 12, 24, 36, 48, 60 and 72 hours after administration of each regime. Ketone in the urine was quantified daily. The duration of hospital stay as well as the side- effects encountered were compared. A total of 60 patients were recruited with 30 patients in each regime. There was no difference in the PUQE score of patients receiving metoclopramide with those receiving combination of promethazine and pyridoxine after 72 hours of drug administration (5.4 ± 1.4 versus 5.3 ± 1.6 respectively, p > 0.05). The duration taken for urine ketone clearance did not significantly differ either (2.03 ± 0.61 days for metoclopramide group versus 2.26 ± 0.63 days for the combination of promethazine and pyridoxine group; p value= 0.15). Both groups of patients have mean hospital stay of about three days. More than half of the patients in the combination of promethazine with pyridoxine group were sedated after the drug administration. Both regimes have similar efficacy as antiemetic in patients with hyperemesis gravidarum, and may be used as the first-line antiemetic in such cases.